Hidroxilação biomimética de hidrocarbonetos catalisada por Mn(III) N-alquilpiridilporfirinas suportadas em sílica-gel ou sílica-gel funcionalizada com grupo cloropropila - Silva, Barbara de Mariz (2021)
Mn(III) porphyrins have been extensively investigated as biomimetic oxidoreductase catalysts for hydrocarbon oxidation. In this work, two classes of catalysts heterogenized in silicas were used as models of cytochrome P450. One class corresponded to the materials containing the three isomers of Mn(III) N- pyridylporphyrins covalently immobilized via quaternization on chromatographic silica gel 60 modified with chloropropyl groups (Sil-Cl) to result in the materials Sil-Cl/MnPY (Y = 1, 2, 3 , corresponding to the ortho, meta and para isomers, in that order). The other class of catalysts corresponded to the materials containing the three isomers of the N-methylpyridinioporphyrins of Mn(III) electrostatically heterogenized in unmodified chromatographic silica gel 60 (SiO2) generating the solids SiO2/MnY (Y = 4, 5, 6, corresponding to the ortho, meta and para isomers, in that order). The catalytic efficiency and selectivity of these six materials were evaluated with respect to the nature of the isomer and the support using the hydroxylation of cyclic or acyclic alkanes (cyclohexane, adamantane and n-heptane) by iodosylbenzene (PhIO) as model reactions. In addition, the oxidation of cyclohexanol to cyclohexanone was also evaluated. Control reactions with the Mn porphyrin precursors under homogeneous conditions were also carried out. The reuse studies showed that the supported catalysts were resistant to oxidative destruction and/or leaching, with little effect on efficiency and selectivity throughout the reuse. In general, Sil-Cl/MnPY materials proved to be more efficient and selective than SiO2/MnPY. This can be associated with the modification of the Sil-Cl silica surface, which renders the material more lipophilic, resembling some the biological features of the cytochromes P450. The results with both Sil-Cl/MnPY (Y = 1, 2, 3) and SiO2/MnY (Y = 4, 5, 6) materials were compared with our previous studies with mesoporous Santa Barbara Amorphous No 15 (SBA-15) silica-based materials, whose reaction conditions are the most closely related to the ones in the current study. The results showed that Sil-Cl/MnPY (Y = 1, 2, 3) and SiO2/MnPY (Y = 4, 5, 6) catalysts were more efficient hydroxylation catalysts than the corresponding materials with SBA-15 and more practical, given the widespread availability and affordability of ordinary chromatographic silica gel 60. All catalysts were evaluated in three consecutive reaction cycles with at least three replicates, showing reproducible catalytic efficiency and robustness. Sil-Cl/MnPY (Y = 1, 2, 3) materials were the most selective toward n-heptane hydroxylation. Among the catalysts, Mn(III) 2-N-pyridylporphyrin immobilized covalently via quaternization to Sil-Cl, Sil-Cl/MnP1, was considered the best catalyst in terms of stability against oxidative destruction, yields, selectivity, and recyclability.